Popular and Elite Religion: the Church and Devotional Control - Gilley, Sheridan (Studies in church history, 2006)
Popular and elite are imprecise terms, but it may be possible to give them a closer definition by relating them to categories in the work of John Henry Newman. In 1877, Newman was growing old. He was republishing his Anglican writings, both to preserve what they contained of value and to draw what poison remained. A particular difficulty attached to his Lectures on the Prophetical Office of the Church, published forty years before, in 1837, which classically defined the peculiar merit of the Church of England as occupying a middle way or via media between Romanism and popular Protestantism. The work contained some sharp attacks on Rome, which Newman had retracted even before his Roman conversion. There remained, however, a particular matter which had long been an obstacle to his submission to Rome, his conviction that the honours which Roman Catholics paid to the Virgin and saints derogated from the unique worship due to Christ, which Newman combined with a fastidious distaste for the more ‘unmanly’ and sentimental or sugary aspects of modern Catholic devotion.